Opportunities for personality-oriented education in learning management systems (Acta Education, 2024)
This article analyzes the functions and functionalities of educational management systems, citing their capabilities in the implementation of personality-oriented learning. Proposals and recommendations have also been developed on the example of the open-source Moodle LMS to determine the personal learning trajectory of learners as well as the use of flexible learning implementation plugins for them.